Электротехнический комплекс для разрядно импульсного синтеза углеродных наноматериалов с различными магнитными свойствами - Богуславский, Л.З.; Назарова, Н.С.; Овчинникова, Л.Е.; Винниченко, Д.В.; Диордийчук, В.В. (Технічна електродинаміка, 2012)
Investigated physical and technical processes in the dischargepulse action on the gases carbon atmosphere to the synthesis ofcarbon nanomaterials with magnetic properties due to the receipt of various allotropic forms of nanocarbon generated by electricalsector. Experimentally determined range of parameters of the magnetic properties of the synthesized nanocarbon. Found that some carbon nano-powders obtained exhibit ferromagnetic properties.